Uterine fibroids, laparoscopic surgery and morcellation. Literature review - Alexander A Seregin; Anastasiia B Nadezhdenskaya; Aleksandra V Asaturova; Dmitry L Ovodenko (IP Berlin A.V., 2019)
Aim. To analyze the literature data on modern approaches to morcellation of myomatous nodes in laparoscopic surgery and to highlight this area in a historical aspect. To form an idea of the main difficulties associated with morcellation, which contributed to and contribute to the improvement of the technique of this manipulation. Materials and methods. The review includes data from foreign articles published in the elibrary.ru and PubMed databases on this topic. Results. It describes both modern trends in the surgical treatment of patients with uterine myoma, and historical aspects of improving methods aimed at reducing risks, reducing the time of surgical intervention and improving its safety. Analyzed data on the use of electromorcellation, carried out both with the use of plastic containers, and without them. Conclusion. High requirements for surgical interventions contributed to the emergence of such a method of intracorporeal fragmentation of drugs, such as morcellation, which led to a significant reduction in the proportion of laparotomic operations in the treatment of patients with my uterus. The introduction of laparoscopy in the surgical treatment of uterine myoma allowed to achieve a fundamentally new high level of rehabilitation of patients. Removing removed drugs from the abdominal cavity is associated with a certain risk. Despite the significant number of proposed methods and devices for morcellation, they all require further improvement, since it is necessary to completely exclude contact of the myoma node tissue with abdominal organs in the extraction process. Currently, active research continues on ways to realize all the benefits of minimally invasive technologies in compliance with the rules of oncological safety.